Roman principles – foundations of the European legal culture and their position in the changing world - Ivančík, Ján (Vilnius University Open Series, 2020)
Roman law is considered to be one of the most influential elements of the continental legal culture. However, rapid technological development and changing social and economic situation bring new challenges for principles tested during the centuries. Consumer protection; fight against corruption and money laundering; data protection and other new fields of law emerge a fundamental question: Are the ancient Roman principles still valid and required?